A Cross-sectional Study of Mother-friendly Hospital Initiatives in Turkey: The Obstetricians and Midwives' Views - Nursen Bolsoy; Mehmet Gulsen; Birgul Celebi Yavas (Mashhad University of Medical Sciences, 2020)
Background & aim: Ministry of Health in Turkey has launched a mother-friendly hospital (MFH) initiative to reduce cesarean section rate, support evidence-based practices, and improve mother-baby friendly maternity care. This study aimed to investigate the views of the obstetricians and midwives using the MFH initiative and measure their job satisfaction levels. Methods: A cross-sectional descriptive design was employed. The data were collected through a questionnaire distributed among 16 obstetricians and 61 midwives working in delivery rooms at four hospitals using the MFH initiative in Turkey. This questionnaire consisted of eight items to elicit participants' characteristics, and another eight items were used to investigate participants' views regarding the MFH setting. The participants' suggestions to MFH initiative, job satisfaction levels and the intention to leave were also measured. Results: The majority of the participants reported that the MFH initiative increase the quality of the maternal services (90.9%) and contributed to their profession (90.9%). Moreover, they stated that their colleagues (84.4%) and pregnant women (94.8%) are satisfied with the MFH. Also, 54.5% of them reported concerns about the MFH initiatives. The mean job satisfaction score was 7.92 (SE=0.26). Significant differences were noted among the participants' job satisfaction in terms of their workload perception, intention to leave, and the workplace (p <0.05). Conclusion: The participants had positive attitudes towards the MFH initiativse and higher levels of job satisfaction. The results suggest that the MFH initiatives are successfully implemented and contributed to maternal services.